A Novel Process to Prepare Chitosan Macrospheres without Shrinkage and its Application to Immobilize β-Galactosidase - Su-Fang Sun; Yan Zhang (E-Journal of Chemistry)
A new process for the preparation of chitosan macrospheres, which was simple and practicable, was suggested in this paper and various chitosans with different molecular weight were used as materials to immobilize β-galactosidase and the chitosan macrospheres with the lowest molecular weight (500 000) was selected as enzyme immobilization carrier based on the highest enzyme activity. In order to overcome the shrinkage of chitosan during drying, the wet macrospheres obtained was treated by 30% glycerol solution for 1 h before drying and the results showed that the dried chitosan macrospheres obtained could keep almost the same structure as its wet form, which was very important for chitosan as enzyme carrier in industry. Finally, β-galactosidase from Aspergillus oryzae was immobilized on above dry chitosan macrospheres and a satisfactory result of the immobilized enzyme was obtained in enzyme activity yield, pH stability, thermal stability, operational stability, Michaelis constants Km and the maximum velocity (Vm)